Quasi‐Experimental Study of Middle School Tokens, Behaviors, Goals, Preferences, and Academic Achievement - Dreger, Kelly Cathleen (My University, 2017)
There is a high demand for standardized instructional strategies that align with decision-making frameworks found in public schools. Teachers who use tokens in the classroom can create more avenues for standardization, provided that their methods address the contradictory nature of past research. A lack of knowledge about reinforcement options and their possible effects has been found within a variety of research studies that attempted to bridge gaps between research and practice. This study aimed to create an incentive system that demonstrated how teachers could use tokens as academic and behavioral supports for students in southwest Georgia. The purpose of this convergent parallel study was to assess the degree to which token use, type, and timing affected performance on nine weeks achievement tests for students in grades 6-8. Additionally, there was an investigation about the extent to which achievement scores were influenced by environmental factors such as the amount of behavioral referrals received, the goals students met to pass tests, and the preferences that students had concerning motivation. Students’ and teachers’ perspectives on tokens were explored throughout this process in order to accurately gather information on their experiences. Overall results for this study showed that those without tokens outperformed students who received tokens during the study. Within the token groups, the highest performers were those who received points in the first half and coins in the second half. Students who received no referrals had better performance and behavior than students who did receive referrals. Students accurately assessed how well they would do on tests, and those who met goals for math performed significantly better than those who did not meet math goals. Motivational preferences alone did not guarantee good performance.
Chapter I: INTRODUCTION 1 | Background 1 | Statement of the Problem.4 | Conceptual Framework 7 | Operant Conditioning 7 | Goal Theory.9 | Purpose of the Study.11 | Research Questions.12 | Significance of the Study 14 | Role of the Researcher 14 | Limitations, Assumptions, and Design Controls 15 | Limitations.15 | Assumptions.16 | Delimitations 17 | Definition of Key Terms.17 | Summary.19 | Chapter II: REVIEW OF RELATED LITERATURE20 | Introduction.20 | Tokens and Academic Achievement.20 | Application of Tokens to Operant Conditioning.22 | Behaviorist Principles 22 | Classical Conditioning and the Behaviorist Movement.22 | Operant Conditioning and Consequences for Tokens.25 | Considerations for Token Design.28 | Token Systems and Behavior Types.28 | Token Use and Behavior Modification.30 | Models for Academic and Behavioral Support.32 | Basic Principles for Schedules of Reinforcement.33 | Scheduling of Tokens in Education 36 | Feedback Combinations 41 | Application of Tokens to Goal Theory 42 | Goal Orientation, Behavior, and Achievement 42 | Token Use and Goal Creation 44 | Token Use and Motivational Preferences 44 | Application of Tokens to Phenomenology 47 | Foundations of Phenomenology.47 | Phenomenology and Tokens 50 | Summary 51 | Chapter III: METHODOLOGY52 | Introduction 52 | Research Design.53 | Design Structure and Worldview.53 | Overview of Mixed Methods Design.53 | Worldview Description 54 | Structure Description.54 | Population and Sample.55 | Participants 55 | Sampling Techniques 56 | Initial Contact.56 | Quantitative Strand.56 | Qualitative Strand.57 | Data Collection.59 | Quantitative Strand 59 | Teacher Training,.59 | Intervention Design and Procedures 60 | Qualitative Strand.65 | Variables and Instrumentation.66 | Variables and Factors.66 | Quantitative Instrument 67 | Qualitative Instrument 68 | Data Analysis and Interpretation.69 | Quantitative Data Analysis.69 | Screening Process 69 | First Round 70 | Second Round.70 | Third Round 71 | Qualitative Data Analysis 72 | Data Mixing.73 | Research Permission and Ethical Considerations 74 | Limitations.75 | Summary 79 | Chapter IV: RESULTS80 | Introduction.80 | Organization of Chapter 80 | Demographics 81 | Ethnicity.82 | Disability Status.84 | ECD Status.85 | Results for Screening.88 | Round 1 Screening 88 | Round 2 Screening 90 | Round 3 Screening 90 | Research Questions 91 | Research Question 1a92 | Finding 1.1.93 | Result 1.194 | Result 1.296 | Result 1.398 | Result 1.4100 | Result 1.5102 | Result 1.6104 | Interpretation of Finding 1.1.106 | Data Mixing for Finding 1.1.107 | Research Question 1b110 | Finding 1.2111 | Result 1.7.112 | Result 1.8.113 | Result 1.9.115 | Interpretation of Finding 1.2.119 | Data Mixing for Finding 1.2.120 | Research Question 2a.122 | Finding 2.1123 | Result 2.1.124 | Result 2.2.126 | Interpretation of Finding 2.1.128 | Data Mixing for Finding 2.1.129 | Research Question 2b132 | Finding 2.2134 | Result 2.3134 | Result 2.4135 | Result 2.5137 | Result 2.6139 | Result 2.7140 | Interpretation of Finding 2.2.143 | Data Mixing for Finding 2.2144 | Research Question 2c.147 | Finding 2.3148 | Result 2.8149 | Interpretation of Finding 2.3.150 | Data Mixing for Finding 2.3.151 | Research Question 3a154 | Finding 3.1156 | Result 3.1156 | Themes for Result 3.1.158 | Interpretation for Result 3.1165 | Result 3.2167 | Themes for Result 3.2168 | Interpretation for Result 3.2.171 | Result 3.3.173 | Themes for Result 3.3.174 | Interpretation of Result 3.3.178 | Research Question 3b.179 | Finding 3.2180 | Result 3.4.181 | Themes for Result 3.4.181 | Interpretation for Result 3.4187 | Result 3.5189 | Themes for Result 3.5.190 | Interpretation for Result 3.5.193 | Result 3.6.195 | Themes for Result 3.6.197 | Interpretation for Result 3.6200 | Result 3.7201 | Themes for Result 3.7203 | Interpretation for Result 3.7.206 | Summary 207 | Research Question 1207 | Research Question 2209 | Research Question 3210 | Chapter V: SUMMARY, CONCLUSIONS, AND RECOMMENDATIONS212 | Summary.212 | Conceptual Framework.214 | Summary of Findings for Research Question 1215 | Summary of Findings for Research Question 2216 | Summary of Findings for Research Question 3219 | Conclusions.220 | Recommendations.225 | Recommendations for Teachers and Students 225 | Recommendations for Researchers.226 | REFERENCES229 | APPENDIX A: Data Collection Timetable.246 | APPENDIX B: Goal Orientation Questionnaire.248 | APPENDIX C: Reinforcement Observation Log 250 | APPENDIX D: Motivational Preferences Check Sheet 252 | APPENDIX E: Teacher Consent Form.254 | APPENDIX F: Parental Consent Form.258 | APPENDIX G: Child Assent Script 262 | APPENDIX H: Interview Guides 265 | APPENDIX I: Prize List Form 271 | APPENDIX J: Institutional Review Board Approval Form 273 |
Keywords: Token economy (Psychology); Middle school education; Academic achievement; School Social Behavior Scales; Goal (Psychology); Preferences (Philosophy)